Recent Advances in Flexible Foam Pressure Sensors: Manufacturing, Characterization, and Applications – a Review - Mohammed Nabeel; Mohanad Mousa; Viskolcz Béla; Fiser Béla; Bela Fiser; Фішер Бейло; Vanyorek László (Taylor & Francis, 2024)
Abstract. The dramatic changes the world and the expectations of potential users have pushed researchers working in flexible foam pressure sensor (FFPS) fabrication to develop more affordable and high-performance materials. Among various materials, polymer foamed-based nanocomposites are a preferred choice due to their excellent mechanical properties, good chemical properties, and easy control. Moreover, the use of nanofillers such as carbon nanotubes (CNTs), carbon black (CB), and graphene in the polymer matrix has greatly improved the properties of the sensors. Therefore, this review focuses on the recent advances in FFPS by using different types of nanofillers in shape and structure. Accordingly, developments in the fabrication of FFPS, including dip coating, spray coating, sputtering, and in situ polymerization are also discussed. Special attention has been paid to identifying the underlying mechanism to maximize pressure sensing and improve the performance of FFPS. Suggestions for future developments in the area of sensing devices applied in health monitoring are also presented.
Editorial board: https://www.tandfonline.com/journals/lmsc20/about-this-journal#editorial-board
Contents: https://www.tandfonline.com/toc/lmsc20/64/2
Keywords: Pressure sensor; pressure sensitivity; nanofiller; polymer matrix; nanocomposite